Improving engineering research quality in Libyan higher education institutions and their role in closing the digital divide - AKHMAAJ, ASMAEIL (E-business technologies conference proceedings, 2021)
This report attempts to uncover the elements that enable Alfateh University to bridge the digital gap and improve the quality of engineering research through successful ICT deployment. The authors investigate the worldwide digital divide, focusing on the inequalities in information technology between developed and developing nations (including Libya), as well as overall rates of social and technical growth. Also, look at the connection between the digital gap and HE instruction, as well as the present state of the digital gap in Libya. It is self-evident that a successful ICT adoption should begin with a thorough grasp of particular faculty demands. The relevance of implementing electronic education at Libyan institutions, as well as the difficulties and solutions to ICT adoption, is then thoroughly investigated. Faculty members should be included at every phase of the design and implementation of cutting-edge technology, according to stakeholders.